PERMAINAN TRADISIONAL MAKA: SOLUSI UNTUK MENGEMBANGKAN KEMAMPUAN MOTORIK ANAK - Maria Fatima Bebhe; Karmelia Rosfinda Meo Maku; Andi Nafsia; Elisabeth Tantiana Ngura (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2026)
The purpose of this study was to determine the motor skills of children before and after being given treatment at Kemala Bhayangkari 08 Bajawa Kindergarten, and to determine the effect of traditional games that can develop children's motor skills at Kemala Bhayangkari 08 Bajawa Kindergarten. This type of research is an experimental method that uses one group pretest posttest design data. The data collection methods used are observation and documentation. The data analysis technique used in this study is descriptive quantitative. This study was conducted at Kemala Bhayangkari 08 Bajawa Kindergarten with a total of 17 children in class B1, consisting of 10 boys and 7 girls. The results showed that the implementation of the traditional gasing game (maka) had positive effect on improving the motor skills of early childhood children. A increase in developmental achievements was seen. Before treatment, children's motor skills were mostly in the categories of beginning to develop (MB) and not yet developed (BB). However, after treatment was given, children's developmental achievements increased to the categories of developing as expected (BSH) and developing very well (BSB). The use of the gasing game was proven to be able to eliminate the category of not yet developed (BB) in the research subjects, so it can be concluded that the traditional gasing game (maka) can be used as an alternative effective learning activity as a stimulus to improve the motor skills of early childhood children.